[PP.15.25] REDO RENAL DENERVATION WITH NON-INVASIVE THERAPEUTIC ULTRASOUND. (September 2017) - Ormiston, J.; Neuzil, P.; O'brien, B.; Saxena, M.; Schmieder, R.E.; Gertner, M.; Dawood, O.; Lobo, M.D.
Abstract : Objective: Safety and preliminary effectiveness evaluation of non-invasive ultrasound (US) renal denervation system in patients who were previously treated with catheter-based radiofrequency renal denervation. Design and method: The Surround Sound system delivers therapeutic US non-invasively to create a field of energy around the renal artery. This mode of delivery is very different from other catheter-based systems which deliver (radiofrequency) energy at concentrated ablation spots. Pre-clinical animal data showed no discernible effects on the renal artery in a repeated treatment model even at doses much higher than used in the clinic. The hypothesis underpinning these data was that the Surround Sound treatment could be safely applied to patients with prior denervation and is potentially well suited for repeated treatments. Eleven patients with uncontrolled hypertension who were previously treated with catheter based renal denervation were treated with the Surround System at 4 centres [U.K (5), Czech Republic (3), Poland (1) and New Zealand (2). Treatment criteria were: office systolic blood pressure (SBP) >160 mm, 24 hour ambulatory SBP > 135 mm Hg, and patients were required to be taking three antihypertensive medications. The patients may or may not have responded to prior renal denervation treatment but all met entry BP criteria. Results: There were no mortality or major adverse events, no significant device related AEs including significant back pain, change in renal function, renal artery stenosis, or other events. At 3 months (11 patients), the average office SBP change was −27.4 mm Hg. At one year (8 patients), the average change in office SBP was −33.4 mm Hg. Average ambulatory SBP change at 6 months (8 patients) was −21.5 mm Hg and −17.2 mm Hg at 1 year (5 patients). Conclusions: These clinical data serve as the initial pilot safety data for redo US renal denervation. Larger randomized trials are needed in this patient population to assess efficacy as well as a treatment regimen in a treatment naïve patient cohort in which planned denervation with the Surround Sound system is studied.